The impact of Baitul Maal wat Tamwil financing in achieving "sejahtera" level to alleviating poverty among mocro-entrepreneurs in west java - Irawan Febianto
Microfinance has always been an essential tool for reducing the poverty level in Indonesia. The poverty level in West Java Indonesia has been decreasing for the past ten years, but at the same time, the reducing level was slowing down. The slow down growth of poverty reduction seems contradictory to the growth of Baitul Maal Wat Tamwil (BMT) as one of the most famous Islamic microfinance institutions in Indonesia. The most significant number of BMT located in West Java with 637 BMTs and their most prominent clients are the micro-entrepreneurs. This raises the question: is there any impact of Islamic microfinance establishment to achieve “sejahtera” level and whether it is also impacting the poverty alleviation in Indonesia. Imam Al-Ghazali divides poverty into two parts: first, poverty concerning material needs; and second, poverty concerning spiritual needs; meanwhile, other scholars define poverty by combining both material and spiritual aspects. This research is intended to fill the gap in the study of poverty alleviation in general, as well as Islamic microfinance on poverty alleviation of micro-entrepreneur, that mostly only measuring the material aspect and not the spiritual aspect. This research also intended to fill the gap by measuring microfinance impact using micro-business as a unit of analysis. This research aimed at measuring micro-business of micro-entrepreneur using “sejahtera” measurement, which covers both material and spiritual aspects, and whether this is in line with poverty alleviation in their household, by comparing it with other well-known poverty alleviation measurements, such as the Poverty Gap Index and Headcount Index. The primary data obtained through survey questionnaires in West Java, Indonesia. The overall results show that there is an improvement of the “sejahtera” level of micro-entrepreneur at their micro-business performance after using BMT financing and the advancement of the “sejahtera” level at business performance positively correlated with alleviating poverty of micro-entrepreneurs household. In the end, this research found that after BMT financing, 27.5 percent of respondents achieved the “sejahtera” level at their business, 47.75 percent achieved a spiritually rich level, 9.25 percent made material only, and 15.5 percent still at an absolute poor level. For their household, after BMT financing, 31 percent of respondents still have income below the poverty line. Using the measurement of “sejahtera” discussed in this thesis, the government can measure the BMT impact in other areas outside West Java. The spiritual aspect can also become an alternative approach in redefining poverty, not only view based on the material but also on spiritual. Therefore the government can also focus its effort on alleviating poverty not only on material poverty but also on spiritual poverty.